Libertad de expresión en los medios privados de la Provincia Los Ríos. Caso La Crónica - Varela Pérez, Blanca María (2019)
One of the important factors for human communication is the way of expressing oneself, so that the media are links to communication looking for alternatives for the general public to keep informed about global events. Free expression is a sovereign right of every free citizen, the same that is exercised according to the needs of the individual, currently the journalist or social communicator, seeks free expression, through the use of social networks, but always The truth of the facts should be considered as a source of perennial search and investigation. In the development of this case study, alternatives will be sought to recognize how freedom of expression is a policy that can be used to exercise journalism, provided that the veracity of the facts is analyzed, in addition to the veracity of the sources from which it was collected information. Social networks are currently a means to carry out community journalism, through citizen complaints that seek to promote good living and a better social environment